Students’ Perspectives on Using E-portfolio for Tertiary-level Academic Writing - Fatema, Kaniz; Nur-A Amanat, Mohammed; Md. Sadman Mobtasin, Munshi (RADINKA JAYA UTAMA PUBLISHER, 2026)
This study investigates student perceptions regarding the implementation of electronic portfolios (e-portfolios) in tertiary-level academic writing courses. Utilizing an experimental research design, the study compares the effectiveness and student experiences of e-portfolios against traditional paper-based portfolios within the L2 writing classroom. The research was conducted on two homogeneous groups enrolled in the